SENTRA SEBAGAI MODEL PEMBELAJARAN UNGGULAN DI PAUD IT SABILAL MUHTADIN BANJARMASIN - Apriani Apri; Ika Irayana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2022)
This study aims to determine the center as a superior learning medel in Islamic PAUD Sabilal Muhtadin Banjarmasin. This research uses a descriptive qualitative approach with tools. Data collectors in the form of observations, interviews, and documentation. Data analysis in this study using the analysis of the Milles and Huberman done inductively, namely drawing conclusions.with the collection stage in the form of voraciously reducing data. Presenting data and verification. The stages of checking the validity of the data in this study used an extension observation, observation persistence, and triangulation. The result of this study indicate that the center is a model superior learning at Islamic integrated PAUD Sabilal Muhtadin Banjarmasin using the center learning model from 2006 until now, application of the center learning model in the islamic Integrated PAUD Sabilal Muhtadin Banjarmasin in accordance with the indicators set. Facilitate children playing about the concept of Early Childhood learning. Because Islamic integrated PAUD Sabilal Muhtadin Banjarmasin once every one to two years sending teachers in turn to Al-Falah Malaka, East jakarta for participating in various trainings in the development of the center learning model and the Islamic integrated PAUD Sabilal Muhtadin Banjarmasin is used as a fence reference schools by other school both from the city of Banjarmasin, Banjarbaru, HSU, Kandamgam and Pelaihari. Factors affecting the center as a superior learning model namely teachers children and media.